ANALISIS PUTUSAN MAHKAMAH AGUNG NO.2871K/PDT/2017 DALAM KASUS PENGINGKARAN AKTA PERJANJIAN PERDAMAIAN NO.04/PDT.G/2000/PN.PROB - Risma Puspita Ningrum; Sofyan Arief; Herwastoeti (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the legal strength of the Peace Agreement Deed No.04/Pdt.G/2000/PN.Prob and to analyze the Supreme Court Decision N0.2871K/Pdt.G/PN.Prob in the case of denial of the peace agreement deed No.04/Pdt.G /2000/PN.Prob in a Legal Perspective, this research uses the Normative Juridical method. The result of this research is that Peace Decision No.04/Pdt.G/2000/PN.Prob has permanent legal force as well as the judge's decision at the final level. in accordance with the provisions of Article 1858 paragraph (1) of the Civil Code Jo. Article 130 paragraph (2) and (3) HIR, and the peace deed, have 3 legal powers, namely binding and final, perfect proof, and executorial power. The District Court's decision was appropriate because the defendant's actions were categorized as illegal actions based on Article 1365 of the Civil Code, this was because the plaintiffs were the legal owners of the disputed land based on the peace decision No.04/Pdt.G/2000/PN/Prob. The Court of Appeal's decision was inaccurate, because it had canceled the peace decision Deed No.4/Pdt.G/2000/PN.Prob in which the peace decision No.4/Pdt.G/2000/PN.Prob had permanent legal force as stipulated in Article 130 HIR, Jo. Article 1858 of the Civil Code, judges of the High Court in passing decisions exceed their authority because the High Court as Judex facti does not have the authority to judge or overturn the final decision, and if the Appellants find new evidence then the legal remedy that can be taken is legal. Article 67 letter b Law No.14 of 1985 concerning the Supreme Court. Furthermore, the Supreme Court's decision was appropriate, because according to the Supreme Court the Judex facti the High Court had wrongly applied the law because it had canceled the Peace Deed No.4/Pdt.G/2000.PN.Prob which had permanent legal force. So that in this case the legal conflict lies in the decision of the High Court